Propriedades antioxidante, antimicrobiana e toxicidade do extrato da casca do alho (Allium sativum L.) - Santos, Paula Correia Medeiros dos (2022)
Garlic (Allium sativum L.) is a spice cultivated since antiquity, widely used both as food and for its medicinal effects. Despite being heavily consumed, much of the research on A. sativum is limited to the study of the bulb and its bulbils, even though the garlic peel corresponds to 25% of the total production and is generally discarded by the industry. In order to obtain a use of this by-product the objective of this work was to elaborate vegetable extracts from the peel of garlic (Allium sativum L.) using maceration and turbolization as extraction methods and water or hydroalcoholic solutions (50% and 70%) as solvents and to evaluate the extracts obtained in relation to the content of bioactive compounds, antimicrobial potential, antioxidant capacity and its toxicity. As a result, garlic peel extracts obtained high levels of phenolic compounds, total tannins, flavonoids and anthocyanins. The hydroalcoholic solutions proved to be more efficient in the extraction of these compounds in relation to the use of aqueous solvents, as well as the maceration method was significantly superior to the turbolization method. This same correlation was obtained in the evaluation of the antioxidant potential, both by ABTS radical capture and by DPPH. Only the hydroalcoholic extracts showed an antimicrobial effect against the gram positive microorganisms Staphylococcus aureus and Listeria monocytogenes, demonstrating bactericidal effects, even at low concentrations (from 3mg/mL). However, although none of the extracts showed acute toxicity, both in relation to the microcrustacean Artemia salina and adult zebrafish (Danio rerio), in the open field test the animals treated with hydroalcoholic extracts (70%) had their motility reduced. Thus, we can conclude that the ETH50% and EMH50% were the most promising extracts, as they presented a high index of bioactive compounds, antioxidant and antimicrobial activity, combined with low toxicity, demonstrating excellent potential for future applications in food matrices.